(3GdoYHGH aj TQM CHjGJ GdBOGHs - (3TQa GdOjf MSf Hf Ydj Hf UGdM GdaOhj (B((3GdYOhj(B)s; (3GHf TeS GdNdGaI , LYaQ Hf eMeO Hf CHh GdaVd (B((3TeS GdNdGag(B) (3eNJGQ GdGaVdj, eLO Gdedc,J (B622 (3g` s
(3ChdgG (B:s
(3aGfj deG hbaJ Ydi cJGH GdBOGH JCdja SfGA Gdedc LYaQ Hf TeS GdNdGaI s
(3BNQgG (B:s
(3hefgG bhd GdeJfHj(B: (3aoQH cFjH djS JfOi Lahfg hoQH cKjQ GdOeY ZjQ cFjH Je GdcJGH Hef Gddg Gdhdj GdhgGH s
(3GdBOGH GdfGaYI HGdCdaGX GdeNJGQI GdLGeYI dLYaQ Hf eMeO GdeYQha HGHf TeS GdNdGaI GdeJhai (B622(3g`s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs